2017
DOI: 10.3390/ijms18050973
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 in Peripheral Artery Disease. Relationships with Markers of Oxidative Stress and Inflammation

Abstract: Galectin-3 is a modulator of oxidative stress, inflammation, and fibrogenesis involved in the pathogenesis of vascular diseases. The present study sought to characterize, in patients with peripheral artery disease (PAD), the localization of galectin-3 in arterial tissue, and to analyze the relationships between the circulating levels of galectin-3 and oxidative stress and inflammation. It also sought to compare the diagnostic accuracy of galectin-3 with that of other biochemical markers of this disease. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Similarly, our study showed that dyslipidemia is a common risk factor for PAD, CVD, and DR, thus suggesting that early attention to and control of dyslipidemia in patients with DR could help to prevent and postpone the onset and progression of macroand microangiopathy and reduce the risk of PAD and CVD. According to the basic research, this result might be due to the fact that dyslipidemia leads to endothelial dysfunction, the increase of oxygen free radicals, and the inactivation of nitric oxide, i.e., oxidative stress [36,37,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our study showed that dyslipidemia is a common risk factor for PAD, CVD, and DR, thus suggesting that early attention to and control of dyslipidemia in patients with DR could help to prevent and postpone the onset and progression of macroand microangiopathy and reduce the risk of PAD and CVD. According to the basic research, this result might be due to the fact that dyslipidemia leads to endothelial dysfunction, the increase of oxygen free radicals, and the inactivation of nitric oxide, i.e., oxidative stress [36,37,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 was shown to induce oxidative stress through the release of O 2 in cultured mast cells, an effect that was blocked by the antioxidant enzyme superoxide dismutase [32]. A study revealed that plasma Gal-3 concentration was increased in peripheral artery disease patients and correlated with F2-isoprostanes, the serologic marker of oxidative stress [33].…”
Section: Gal-3 and Oxidative Stress The Relationship Betweenmentioning
confidence: 99%
“…Additionally, the plasma levels of galectin‐3 are increased in carotid atherosclerotic patients . In particular, it is expressed in adventitia in normal arteries but displaced by media and the intima in patients with peripheral arterial disease suggesting the involvement of galectin‐3 in the site of the atherosclerosis plaque formation . On the contrary, the inhibition of galectin‐3 by either gene inactivation or therapeutic modulation to reduce lesion size in apolipoprotein E‐deficient mice is mainly attributed to the diminishment of its proinflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…18 In particular, it is expressed in adventitia in normal arteries but displaced by media and the intima in patients with peripheral arterial disease suggesting the involvement of galectin-3 in the site of the atherosclerosis plaque formation. 10 On the contrary, the inhibition of galectin-3 by either gene inactivation 19 or therapeutic modulation 20 to reduce lesion size in apolipoprotein E-deficient mice is mainly attributed to the diminishment of its proinflammatory properties. A recent study reveals that galectin-3 exacerbates oxLDL-mediated endothelial injury by inducing inflammation via integrin β1-RhoA-JNK signaling activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation